The effectiveness of cartoon video distraction in reducing pain levels in children during the intravenous injection process - Hadi Hasbulloh, Bahtiar Firmansah; Irdawati, Irdawati (Fakultas Ilmu Kesehatan, 2023)
Children's health care in hospitals requires special techniques in the treatment process, this is based on the psychology of children who are not yet mature enough to accept new things. During treatment, children often experience severe trauma due to invasive procedures carried out by health workers. Intravenous injection is an invasive procedure that causes pain. Non-pharmacological interventions play an important role in overcoming this problem, audiovisual distraction watching cartoon videos could be an option to prevent the trauma they feel. The research problem focuses on the level of pain felt by children during the intravenous injection process at the inpatient hospital at INDRIATI Hospital, Sukoharjo Regency. The aim of this study was to determine the effectiveness of the distraction of watching cartoons on pain levels during the intravenous injection process. This research method is quantitative research. In measuring pain levels, researchers used the Wong Baker scale and involved 10 children as subjects in the research. The research results showed that children tended to experience moderate pain after the intervention of watching cartoon videos.